Integrasi Artificial Intelligence untuk Personalisasi Bahan Ajar Bahasa Arab sesuai Kebutuhan Pembelajar - Muhammad Husen Z; Andi Abdul Hamzah (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the integration of Artificial Intelligence (AI) in Arabic language learning with a focus on personalizing teaching materials according to learner needs. The background of this research is based on the challenges in teaching Arabic which include the diversity of students' backgrounds. The research was conducted with a descriptive qualitative approach through observation, interview, and documentation study of the AI platform. The results show that AI is able to analyze students' strengths and weaknesses, provide adaptive content, and increase learning motivation. This study concludes that AI can be an effective tool in supporting more personalized and relevant Arabic language learning. Recommendations include teacher training, gradual adoption of technology, and development of local AI-based platforms.